The legislative role of the head of state in the mixed political system: a case study of France: international and political journal - Abdul Rahman , Lecturer Dr. Abdul Juma (The International and Political Journal, 2024)
The mixed system is the constitutional system that combines the characteristics and techniques of government in both the parliamentary and presidential systems. It is the system that is based in its origin on the parliamentary system in introducing the techniques of the presidential system, where the executive authority has been strengthened, especially the powers of the head of state, who has come to enjoy broader powers than the head of state enjoys in the traditional parliamentary system, so that they have become close to those enjoyed by the head of state in the presidential system, and this is what some jurists have called this model of systems the (semi-presidential) system. This system is concerned with combining the compatible elements between these two systems in a way that does not create a conflict between them, but rather a synthesis and harmony. Perhaps one of its most prominent models is the system in force in France under its Fifth Republic according to the 1958 Constitution. The Fifth Republic was formed in France with a new constitution that granted great powers to the president, and the presidency of the republic became the center of power in the government, a role usually occupied by parliament.